1992
DOI: 10.1111/j.1365-2958.1992.tb01793.x
|View full text |Cite
|
Sign up to set email alerts
|

Broad‐host‐range Rhizobium species strain NGR234 secretes a family of carbamoylated, and fucosylated, nodulation signals that are O‐acetylated or sulphated

Abstract: Rhizobium species strain NGR234 is the most promiscuous known rhizobium. In addition to the non-legume Parasponia andersonii, it nodulates at least 70 genera of legumes. Here we show that the nodulation genes of this bacterium determine the production of a large family of Nod-factors which are N-acylated chitin pentamers carrying a variety of substituents. The terminal non-reducing glucosamine is N-acylated with vaccenic or palmitic acids, is N-methylated, and carries varying numbers of carbamoyl groups. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
163
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(168 citation statements)
references
References 43 publications
2
163
0
2
Order By: Relevance
“…The first deformation occurs within 1 h after Nod factor application, whereas an increased cytoplasmic streaming occurs within 30 min (data not shown). In most other studies, root hair deformation was first scored several days after Nod factor application (Lerouge et al, 1990;Spaink et al, 1991;Price et al, 1992;Sanjuan et al, 1992;Schultze et al, 1992;Mergaert et al, 1993). Therefore, it is not clear whether such studies provide an accurate comparison of the abilities of different Nod factors to induce deformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first deformation occurs within 1 h after Nod factor application, whereas an increased cytoplasmic streaming occurs within 30 min (data not shown). In most other studies, root hair deformation was first scored several days after Nod factor application (Lerouge et al, 1990;Spaink et al, 1991;Price et al, 1992;Sanjuan et al, 1992;Schultze et al, 1992;Mergaert et al, 1993). Therefore, it is not clear whether such studies provide an accurate comparison of the abilities of different Nod factors to induce deformation.…”
Section: Discussionmentioning
confidence: 99%
“…105, 1994 deformation was scored 3 h after inoculation with R. leguminosarum bv trifolii and these deformed root hairs were present in a zone located 2 to 5 mm from the tip (Bhuvaneswari and Solheim, 1985). However, in a11 but one (Firmin et al, 1993) of the studies to determine Nod factor activity, root hair deformation was examined severa1 days after addition of Nod factor (Lerouge et al, 1990;Spaink et al, 1991;Price et al, 1992;Sanjuan et al, 1992;Schultze et al, 1992;Mergaert et al, 1993).…”
Section: Research (Nwo)mentioning
confidence: 99%
“…The first stage of this interaction leads to the activation of bacterial nodulation (nod) genes by plant flavonoids. The nod genes are involved in the production ofNod factors (1)(2)(3)(4)(5)(6), which act as host-specific signals to trigger nodule formation (1,2,5,7,8). The backbone of all Nod factors consists of an N-acetylglucosamine oligosaccharide (three to five sugar residues) from which the acetyl group at the nonreducing end is replaced by an acyl chain.…”
mentioning
confidence: 99%
“…It was originally thought that Rhizobium synthesizes only minute quantities of CLOSs and excretes them into the extracellular milieu where they can act on the host plant (3,4,13). However, we recently found that CLOS glycolipids can be purified in significantly higher yield (Ͼ1000-fold) from extracts of cell membranes of wild-type rhizobia than from culture supernatants (14,15).…”
mentioning
confidence: 96%